Fexofenadine hydrochloride in the treatment of allergic disease: a review - David Axelrod (Journal of Asthma and Allergy, 2008)
David Axelrod1, Leonard Bielory2Division of Allergy, Immunology and Rheumatology, UMDNJ-New Jersey Medical School, 1Department of Medicine, 2Departments of Medicine, Pediatrics, Ophthalmology and Visual Sciences, Newark, New Jersey, USAAbstract: Fexofenadine is a selective, non-sedating H1 receptor antagonist, marketed in the United States since 2000. The FDA approved an oral suspension in 2006, for the treatment of seasonal allergic rhinitis and chronic idiopathic urticaria in children. The tablet, capsule, and oral suspension are bioequivalent. Although fexofenadine does not use P450 CYP 3A4 it does interact with a number of drugs at P-glycoprotein and organic anion transporter polypeptides. The risk of toxicity from other drugs may increase with the administration of fexofenadine. Orange and grapefruit juices reduce the bioavailability of fexofenadine. Fexofenadine has been shown to have an impact on inflammatory mediators, other than histamine, such as decreasing the production of LTC4, LTD4, LTE4, PGE2, and PGF2α; inhibiting cyclo-oxygenase 2, thromboxane; limiting iNOS generation of NO; decreasing cytokine levels (ICAM-1, ELAM-1, VCAM-1, RANTES, I-TAC, MDC, TARC, MMP-2, MMP-9, tryptase); and diminishing eosinophil adherence, chemotaxis, and opsonization of particles. These effects may provide benefit to some of the inflammatory responses of an acute allergic reaction and provide a basis for future development of H1 antagonists with stronger anti-inflammatory effects. These studies also support the contention that fexofenadine is effective for the treatment of allergic rhinits and chronic idiopathic urticaria.Keywords: fexofenadine, allergy, oral suspension, formulations, pharmacology